Iron oxide nanoparticles as a drug carrier reduce host immunosuppression for enhanced chemotherapy. Issue 12 (7th March 2022) - Zhou, Benqing; Liu, Jinxing; Wang, Lu; Wang, Meng; Zhao, Chong; Lin, Haoyu; Liang, Yuanke; Towner, Rheal A.; Chen, Wei R.
Abstract : BSA-bioinspired iron oxide nanoparticles as a nanocarrier to load anticancer drug mitoxantrone for enhanced chemotherapy with low levels of immunosuppression. Abstract : Chemotherapy is still regarded as the main modality for cancer treatment. However, it often suppresses the host immune system, resulting in limited therapeutic effects. It is desirable to design a novel chemotherapeutic agent to reduce the level of immunosuppression. Herein, we designed bovine serum albumin (BSA)-bioinspired iron oxide nanoparticles (IONPs) as a nanocarrier to load anticancer drug mitoxantrone (MTX) for enhanced chemotherapy of orthotopic breast cancer. The treatment with IONPs@BSA–MTX complexes increased CD3 + CD4 + and CD3 + CD8 + T lymphocytes more than free MTX. The complexes effectively restored the host immune system and exhibited a better anticancer efficacy than free MTX. It was worth noting that the BSA-inspired IONPs were a satisfactory contrast agent for magnetic resonance imaging of tumors and lymph nodes. Our work provides a novel strategy for enhanced chemotherapy with low levels of immunosuppression in the treatment of breast cancer and other cancers.